Abdominal Aortic Occlusion and the Inflammatory Effects in Heart and Brain - Jun Xu; Sijie Li; Alexandra Wehbe; Xunming Ji; Yong Yang; Yu Yang; Linhui Qin; Feng-Yong Liu; Yuchuan Ding; Changhong Ren (Mediators of Inflammation)
Background. Abdominal aortic occlusion (AAO) occurs frequently and causes ischemia/reperfusion (I/R) injury to distant organs. In this study, we aimed to investigate whether AAO induced I/R injury and subsequent damage in cardiac and neurologic tissue. We also aimed to investigate the how length of ischemic time in AAO influences reactive oxygen species (ROS) production and inflammatory marker levels in the heart, brain, and serum. Methods. Sixty male C57BL/6 mice were used in this study. The mice were randomly divided into either sham group or AAO group. The AAO group was further subdivided into 1–4 hr groups of aortic occlusion times. The infrarenal abdominal aorta was clamped for 1–4 hr depending on the AAO group and was then reperfused for 24 hr after clamp removal. Serum, hippocampus, and left ventricle tissue samples were then subjected to biochemical and histopathological analyses. Results. AAO-induced I/R injury had no effect on cell necrosis, cell apoptosis, or ROS production. However, serum and hippocampus levels of malondialdehyde (MDA) and lactate dehydrogenase (LDH) increased in AAO groups when compared to sham group. Superoxide dismutase and total antioxidant capacity decreased in the serum, hippocampus, and left ventricle. In the serum, AAO increased the level of inducible nitric oxide synthase (iNOS) and decreased the levels of anti-inflammatory factors (such as arginase-1), transforming growth factor- β1 (TGF-β1), interleukin 4 (IL-4), and interleukin 10 (IL-10). In the hippocampus, AAO increased the levels of tumor necrosis factor (TNF-α), interleukin 1β (IL-1β), interleukin 6 (IL-6), IL-4, and IL-6, and decreased the level of TGF-β1. In the left ventricle, AAO increased the level of iNOS and decreased the levels of TGF-β1, IL-4, and IL-10. Conclusions. AAO did not induce cell necrosis or apoptosis in cardiac or neurologic tissue, but it can cause inflammation in the serum, brain, and heart.